1988
DOI: 10.1007/bf00199942
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serial determinations of circulating immune complex levels in malignant melanoma

Abstract: A total of 50 melanoma patients free of distant metastatic disease and 54 healthy controls were analyzed for circulating immune complexes (cIC) and complement split product (C3d), using solid-phase Clq-anti-IgG radioimmunoassay (RIA), Clq-protein A RIA, and anti-C3d anti-IgG RIA for cIC detection. No significant differences in cIC and C3d levels could be demonstrated between the controls and the 31 patients with primary malignant melanoma analyzed before surgery. To evaluate the prognostic value of serial meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Circulating immune complexes (CIC) have been reported in the serum of patients with malignancies [60,61], but the occurrence of immune complex-mediated disease has been reported infrequently. The presence of CIC have been thought to indicate advanced stage or dissemination of disease [62], but in a recent prospective study, CIC were not found to be indicative of tumor recurrence in either melanoma or breast carcinoma [63]. Nephrotic syndrome secondary to CIC deposition has been reported in patients with non-Hodgkin's lymphoma.…”
Section: Immune Complex Diseasementioning
confidence: 99%
“…Circulating immune complexes (CIC) have been reported in the serum of patients with malignancies [60,61], but the occurrence of immune complex-mediated disease has been reported infrequently. The presence of CIC have been thought to indicate advanced stage or dissemination of disease [62], but in a recent prospective study, CIC were not found to be indicative of tumor recurrence in either melanoma or breast carcinoma [63]. Nephrotic syndrome secondary to CIC deposition has been reported in patients with non-Hodgkin's lymphoma.…”
Section: Immune Complex Diseasementioning
confidence: 99%